Seasonal variability of coastal pH and CO2 using an oceanographic buoy in the Canary Islands - González, Aridane G.; Aldrich-Rodríguez, Ariadna; González-Santana, David; González-Dávila, Melchor; Santana-Casiano, J. Magdalena (Frontiers in Marine Science, 2024)
The present study focuses on the ongoing monitoring effort that started in March 2020 along the east coast of Gran Canaria, within the Gando Bay, by the CanOA-1 buoy with the collection of multiple variables within the CO2 system, such as CO2 fugacity (fCO2), pH (in total scale, pHT), total inorganic carbon (CT), and other hydrographic variables including sea surface salinity (SSS), sea surface temperature (SST) and wind intensity and direction. Accordingly, the study allows the computation of the CO2 flux (FCO2) between the surface waters and the atmosphere. During the study period, stational (warm and cold periods) behavior was found for all the variables. The lowest SST values were recorded in March, with a range of 18.8-19.3ºC, while the highest SST were observed in September and October, ranging from 24.5-24.8ºC. SST exhibited an annual increase with a rate of 0.007ºCyr-1. Warmer months increased SSS, while colder periods, influenced by extreme events like tropical storms, led to lower salinity (SSS=34.02). The predominant Trade Winds facilitated the arrival of deeper water, replenishing seawater. Atmospheric fCO2 averaged 415±4 µatm (2020-2023). Surface water fCO2sw presented variability, with the highest values recorded in September and October, peaking at 437 µatm in September 2021. The lowest values for fCO2sw were found in February 2021 (368 µatm). From 2020 to 2023, surface water fCO2sw values displayed an increasing rate of 1.9 µatmyr-1 in the study area. The assessment of fCO2sw decomposition into thermal and non-thermal processes revealed the importance of SST on the fCO2sw. Nevertheless, in the present study, it is crucial to remark the impact of non-thermal factors on near-shallow coastal regions. Our findings highlight the influence of physical factors such as tides, and wind effect to horizontal mixing in these areas. The CT showed a mean concentration of 2113±8 μmolkg-1 and pH at in-situ temperature (pHT,IS) has a mean value of 8.05±0.02. The mean FCO2 from 2020 to 2023 was 0.34±0.04 mmolm-2d-1 (126±13 mmolm-2yr-1) acting as a slight CO2 source. Extrapolating to the entire 6 km2 of Gando Bay, the region sourced 33±4 Tons of CO2 yr-1.